How does a nursing crisis management intervention impact relatives' experiences in two trauma centres? A time-series study - Mia Blaabjerg; Anne Sophie Ågård; Marianne Lisby (Elsevier, 2024)
Background: Being a relative to a trauma patient may be a dramatic experience. Often, trauma centre nurses do not feel they have the competences needed to meet relatives experiencing a crisis. Therefore, a need exists to enhance their crisis management competencies. Objective: To investigate relatives' experiences of a nursing crisis management intervention on information, inclusion and support, including the importance of these needs in two Danish trauma centres. Design: A prospective intervention study based on interrupted time series. The intervention, conducted in 2020-2021, consisted of a crisis management training programme. Setting(s): The Trauma Centre of the Aarhus University Hospital and Aalborg University Hospital in Denmark. Participants: Relatives (18+ years) of critically ill or injured patients (n = 293). Methods: Data were collected using a 32-item questionnaire. The primary outcome was relatives' overall experience of the quality of the information, inclusion and support measured on a visual analogue scale (VAS) (0-10). Secondary outcomes were changes in risk ratios and scores between the periods for each of the three main variables. The outcome was measured as weighted and non-weighted scores, taking into account the importance of each variable. Besides use of interrupted time series, predictive and weight-adjusted analyses were performed. Time series comprised a before-period (6 months), an implementation period (3 months) and an after-period (6 months). Due to ceiling effect, the predictive analysis was dichotomized using the median scores for information, inclusion and support. Results: Overall, no differences were observed between the participants' characteristics in each of the three periods. Comparing the implementation period with the after-period revealed a statistically significant positive difference between the relatives' assessment of crisis management [p = 0.009]. Additionally, the probability of scoring >8 from before to after the intervention increased statistically significantly [Risk ratio 1.21, 95 % confidence interval 1.16-1.27]. The secondary outcomes showed that the greatest change over time was inclusion of relatives [Risk ratio, 1.25 95 % confidence interval 1.15-1.35]. Information had the greatest effect on relatives' experience of nurses' provision of crisis management and was also the needs area that relatives considered most important. However, information was also the needs area that evolved least during the study. Conclusions: Based on the selected cut-off levels, the intervention appeared to have a positive effect on relatives' experiences - especially inclusion of relatives. In the weighted analyses, information was considered most important and also had the greatest effect on relatives' overall experience. Nurses' crisis management competencies should be prioritized in trauma centres.